1991
DOI: 10.1017/s0950268800067522
|View full text |Cite
|
Sign up to set email alerts
|

Surveys of human enterotoxigenicEscherichia colifrom three different geographical areas for possible colonization factors

Abstract: Enterotoxigenic Escherichia coli (ETEC) from Burma, central Africa (Rwanda and Zaire) and Peru, were screened by enzyme-linked immunoassays for the colonization factor antigens (CFAs) and putative colonization factors (PCFs): CFA/I, CFA/II, which consists of three coli surface-associated (CS) antigens, CS1, CS2 and CS3, CFA/III, CFA/IV (CS4, CS5, CS6), CS7, PCFO9, PCFO159. H4, PCFO166, and CS17. The highest proportion of ETEC with identifiable colonization factors (71%) were found in the strains from Burma, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
51
1

Year Published

1992
1992
2005
2005

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(60 citation statements)
references
References 33 publications
8
51
1
Order By: Relevance
“…In this study, all 6 CFA/II strains presented CS1CS3, and five belonged to serotype 06 : H 16. In Argentina, the pattern CS1CS3 was more common than any other CFA/II pattern, also occurring mostly in 06 : H16 strains, but in Burma and Peru the CS1CS3 pattern did not occur, and all O6 : H16 strains presented CS2CS3 (2,27).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…In this study, all 6 CFA/II strains presented CS1CS3, and five belonged to serotype 06 : H 16. In Argentina, the pattern CS1CS3 was more common than any other CFA/II pattern, also occurring mostly in 06 : H16 strains, but in Burma and Peru the CS1CS3 pattern did not occur, and all O6 : H16 strains presented CS2CS3 (2,27).…”
Section: Discussionmentioning
confidence: 88%
“…Similarly, in the other study from Sdo Paulo, CFA/I was more common than CFA/II (30). CFA/I was also the most frequently identified type in Chile, Argentina, and Burma (1,2,27). However, in Central Africa and Peru CFA/IV was the most common type identified, and some PCFs also occurred in elevated frequencies (27).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Strains of E. coli 0159 have been found in studies of travellers' diarrhoea [6], in surveys of the occurrence of human ETEC in underdeveloped areas [24] and from outbreaks of E. coli-associated diarrhoea [25,26]. These strains had the flagellar antigens 20 or 37, or were non-motile.…”
Section: Properties Of Etec Strains Isolatedmentioning
confidence: 99%
“…Only three strains in this study (6 %) had no identifiable colonization antigen, and two of them produced only LT. It has been suggested that strains of this type may produce less severe diarrhoea or may be nonpathogenic [24]. In the study of Wolf and colleagues [23] a much larger proportion of the ETEC strains (25 %) did not express a colonization antigen detectable by the assays used.…”
Section: Properties Of Etec Strains Isolatedmentioning
confidence: 99%